WORLD EXPERIENCE OF UNIVERSITY SUSTAINABLE DEVELOPMENT - Nataliia Kholiavko; Iryna Didenko (Economics & Education, 2023)
Introduction. A typical practice of the world's leading countries is the transformation of higher education institutions into agents of change in society. In the XXI century, these changes are primarily focused on various aspects of sustainable development of the country and its regions. Currently, it is the universities, together with NGOs, that have the greatest impact on the achievement of the Sustainable Development Goals proclaimed by the UN for 2015. The purpose of the research is to analyse the global experience of sustainable development in higher education institutions (HEIs). Methodology. This study used the cognitive method of analysis. In order to obtain the most objective research results, the authors studied the universities included in the international Times Higher Education Impact Rankings. The study covered universities from all over the world that were included in the top 50 of the rating. The results of the analysis are systematised according to geography (the article includes several sections characterising the sustainable development of universities in Europe, the United States, Canada and Australia). Results. Higher education institutions are now expected to become leaders in sustainable change in the country, economy and society. The world's leading universities are demonstrating how to progressively transform their activities in line with sustainable principles. They are investing heavily in the implementation of the latest technologies for energy saving, water conservation, campus landscaping and waste recycling. Since they have access to areas where the natural complex is preserved, universities are trying to support these areas and create favourable conditions for using them as living laboratories in educational and research processes. Universities offer sustainable development and lifestyles as part of their educational activities (public lectures, expert workshops, specialised short-term online training, etc.). Universities influence the achievement of the Sustainable Development Goals through their educational and research (inventive) activities. The world's leading universities are keen to promote the concept of sustainable development: they share events held, projects and initiatives undertaken and goals achieved widely on their official websites and social networks. Conclusion. The main directions of sustainable development in higher education institutions are 1) sustainable development of the campus (carbon neutrality, rational consumption, energy efficiency, waste recycling, optimisation of drinking water consumption, green transport, food safety for students); 2) sustainable educational programmes and courses (a sustainable component in students' bachelor and master theses); 3) sustainable research (innovative technologies against climate change, water conservation, energy saving, etc.); 4) management (internal regulatory documents on sustainable development, specialised sustainability centres to promote and support sustainable initiatives). Long-term partnership with stakeholders (entrepreneurs, local authorities and students as agents of future sustainable change) plays an important role in ensuring sustainability. The sustainable development strategy of a modern higher education institution should be based on the principles of complexity and coherence, which will not allow sustainability measures and initiatives to be fragmented and asynchronous. Areas for further research include building a theoretical and methodological framework for the development of an integrated ecosystem of sustainable development of universities.